THE USE OF WAVE GYMNASTICS TO INCREASE THE LEVEL OF HEALTH OF STUDENTS - YARUSHIN S.A (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2019)
The use of innovative means in the process of physical education of higher education students, on the one hand, should not make it difficult to organize training sessions, and on the other, the use of new methods and means of their implementation designed to improve the efficiency of the process of formation and preservation of students ‘ health. In this context, we have experimentally established that the correction of previously used techniques of using Agashin simulators significantly enhances the effects of biomechanical resonance provided by wave mechanical action. At the same time, using exercises of a cyclic nature, it is possible to achieve a more pronounced effect of coordination and normalization of the processes of functioning of various systems of the human body (respiratory, cardiovascular, etc.).